Assessment of healthcare professionals’ skills in pain management in Meru Teaching and Referral Hospital and St Theresa Mission Hospital Kiirua, Kenya (African Journal of Science, Technology and Social Sciences, 2025)
ABSTRACTBackground: Pain is a public health problem and affects millions of people globally. According to Bisher et al 2023, analysed medical literature reveals a concerning gap of up to 30% of healthcare professionals lack training in pain assessment and management. Effective pain management is essential and possible through comprehensive pain management guidelines, trained healthcare professionals and adequate facilities. Studies suggest that health care professionals often demonstrate varying skills in pain assessment and management and consequently inadequately managed pain. Therefore, this study aimed to assess the healthcare professionals’ Skill in pain management in Meru Teaching and Referral hospital and St Theresa mission hospital Kiirua. Methods: Design was a Cross-sectional study (Mar 23 – May5, 2025). Participants included 140 HCPs (22 doctors, 33 clinical officers, 102 nurses).Tool Used was Adopted KASRP questionnaire and modified practice questions from literature review and a checklist to validate skill practice.  Ethical approval from MIRERC, NACOSTI, Meru County Research office and a consent from participants were sought. Analysis was by descriptive, Chi-square, logistic regression, and multinomial logistic regression at a Significance set at p < 0.05. Results:  N= 135. 17(89.5%) out of 19 questions assessing the HCPs skills in pain management were answered correctly.  129(95.6%) participants reported to often follow guidelines to effectively manage pain in their unit and 56 (41.5%) of healthcare professionals reported to use the pain assessment tool every time they meet the patients. Inferential statistics found lack of significant pairwise differences in practice by designation. Mean Differences = 0.15079, Sig. = 0.992 Mean Difference = -1.37143, Sig. = 0.444. There was a significant difference between the KASRP score, sample characteristics and the checklist results where (p
Keywords: Pain Management skills, Healthcare Professionals, Pain assessment scales, Meru Teaching and Referral Hospital St. Teresa Mission Hospital Kiirua